X-ray diffraction studies on fiber of oil palm empty fruit bunch and rubberwood for medium-density fiberboard - Deraman, M.; Zakaria, S.; Husin, M.; Aziz, A. A.; Ramli, R.; Mokhtar, A.; Yusof, M. N.M.; Sahri, M. H. (Kluwer Academic Publishers, 1999)
Alternative materials to rubberwood (RWD) fiber particularly fibers from oil palm empty fruit bunch (EFB) in producing such fiberboards were studied. However, boards prepared from the EFB fiber failed to satisfy the thickness swelling and water absorption tests. The cellulose in both EFB and RWD fibers was studied using the X-ray diffraction method. Its principle is that the crystalline and amorphous cellulose in the fiber will have sharp and broad peaks, respectively. In the crystalline region, the cellulose chains are arranged orderly in a three-dimensional crystal lattice and in the amorphous region, the chains have much less orientation with respect to each other. The diffraction profile for the EFB and RWD samples are interpreted and discussed.